1976
DOI: 10.1097/00000658-197604000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Effect on Hepatic Carbohydrate Metabolism in the Endotoxin-Shocked Monkey

Abstract: This study investigated the effect of glucocorticoid treatment on survival, on hepatic carbohydrate metabolism, and on levels of hepatic adenine nucleotides in the endotoxin-shocked monkey. Dexamethasone sodium phosphate (DMP) administered either at the time of endotoxin challenge or up to 90 minutes afterward significantly increased the survival rates. Endotoxin administered alone caused profound hypoglycemia and lactic-acidemia, which were alleviated by the administration of DMP. Endotoxin administered alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0
4

Year Published

1977
1977
1987
1987

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 24 publications
2
8
0
4
Order By: Relevance
“…More severe infections also inhibit gluconeogenesis, thus increasing the risk that glucose production will not keep pace with glucose utilization. Bacterial endotoxins can inhibit several enzymes required for gluco neogenesis, including phosphoenolpyruvate carboxykinase, fructose-1,6-diphosphatase, and glucose-6-phosphatase [Schuler et al, 1976].…”
Section: Discussionmentioning
confidence: 99%
“…More severe infections also inhibit gluconeogenesis, thus increasing the risk that glucose production will not keep pace with glucose utilization. Bacterial endotoxins can inhibit several enzymes required for gluco neogenesis, including phosphoenolpyruvate carboxykinase, fructose-1,6-diphosphatase, and glucose-6-phosphatase [Schuler et al, 1976].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin, which stimulates the uptake of glucose and amino acids by cells and enhances glycogen synthesis, renders mice more susceptible to the lethal action of endotoxin (25). On the other hand, glucocorticoids have been reported to ameliorate the lethal effects of endotoxin in humans and animals (4,32,35).…”
mentioning
confidence: 99%
“…It has been reported (4,30,41) that the glycogen depletion and the hypoglycemia were associated with changes in activities of enzymes involved in glycogen synthesis and glucose metabolism. Many workers (15,43,44) have suggested that gluconeogenesis was impaired by the administration of endotoxin. On the other hand, Woods et al (53) showed that Salmonella endotoxin exerted a stimulatory effect on tumor glycolysis similar to the action of insulin.…”
mentioning
confidence: 99%